A Low‐Surface‐Tension Strategy to Construct Ultrathin Reduced Graphene Oxide as Lithiophilic Matrix for Lithium Metal Anode. Issue 24 (27th July 2022) - Zhang, Ying; Sun, Jing; Liu, Wen; Niu, Zanyao; Yan, Yang; Qiao, Lizhen; Wu, Na
Abstract: Lithium metal is regarded as "holy grail" in the secondary rechargeable batteries. However, irregular Li deposition and dead lithium during the plating/striping process lead to serious safety issues and rapid capacity decay. The low conductivity of matrix and inhomogeneous ion transfer result in the growth of lithium dendrite and thus the low coulombic efficiency. Here, the authors propose to solve this issue by constructing highly conductive matrix with regulated charge transfer. A low surface tension (LST) strategy is adopted to construct ultrathin reduced graphene oxide (UrGO) to storage Li. The ultrathin and loose structure promise UrGO with high conductivity and the uniformly distributed residue oxygen‐containing groups helps to induce the uniform deposition of lithium due to the improved affinity to Li. The obtained UrGO with high conductivity shows a low lithium nucleation overpotential. The UrGO@Li electrode reveals an outstanding electrochemical stability with a high coulombic efficiency of 98.5% for over 300 cycles. The good performances of full cell also indicate the successful design of the UrGO matrix and the LST strategy provides a new vision for designing highly conductive graphene‐based porous materials. Abstract : A lithiophilic ultrathin reduced graphene oxide (UrGO) with uniformly‐distributed lithiophilic O‐containing functional groups is constructed via a low‐surface‐tension strategy. The UrGO shows a high charge transfer ability with an ultrathin and amorphous structure as well as a high C/O ratio. The fast charge transfer and fluffy morphology promise the uniform deposition of lithium metal.